2006
DOI: 10.1103/physrevb.73.125103
|View full text |Cite
|
Sign up to set email alerts
|

Effective refractive index and group velocity determination of three-dimensional photonic crystals by means of white light interferometry

Abstract: White-light interferometry measurements over a wide spectral range in the optical region have been performed on three-dimensional ͑3D͒ opal-based photonic crystals that have permitted extracting the optical phase delay introduced by samples with an increasing number of layers. The absolute phase that corresponds to the wave vector inside the samples has been obtained by a proper normalization procedure. From the absolute phase and the transmittance, we have determined the complex effective refractive index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
45
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 34 publications
8
45
0
Order By: Relevance
“…These features have been repeatedly observed for a large number of samples, hence confirming the relation between film growth speed, crystal thickness and density of intrinsic defects in colloidal crystal films. Other groups have recently reported thorough analyses of the variations of crystal thickness along the growth direction 21,25 or of the relation between crystal thickness and defect density or domain size, 23,26 such observations being in fair agreement with those reported in ref. 18 and 19. A complete picture of the film growth process still lacks a description of the ordering of microspheres in a facecentred-cubic lattice within a receding meniscus.…”
Section: 21supporting
confidence: 85%
See 1 more Smart Citation
“…These features have been repeatedly observed for a large number of samples, hence confirming the relation between film growth speed, crystal thickness and density of intrinsic defects in colloidal crystal films. Other groups have recently reported thorough analyses of the variations of crystal thickness along the growth direction 21,25 or of the relation between crystal thickness and defect density or domain size, 23,26 such observations being in fair agreement with those reported in ref. 18 and 19. A complete picture of the film growth process still lacks a description of the ordering of microspheres in a facecentred-cubic lattice within a receding meniscus.…”
Section: 21supporting
confidence: 85%
“…2(a) (dashed line), it is necessary to introduce certain extinction in the structure through an imaginary part of the refractive index of the spheres Im(n). 22,23 In fact, it can be rigorously demonstrated that losses in the form of diffusely scattered light, introduced, for instance, by imperfections such as particle size dispersion or vacancies, can be approximated by such imaginary part of the refractive index of the spheres for weakly disordered systems. 24 Thus, in our case Im(n) is an extinction coefficient directly related to the density of intrinsic defects in the structure.…”
Section: 21mentioning
confidence: 99%
“…It should be noted that the amount of disorder present in colloidal crystal films has previously been approximated by assuming an optical extinction factor that accounts for imperfections in the lattice. 18,19 The most remarkable result of these two precedents was that the amount of disorder is smaller for thicker sample. Our study indicates that the thicker regions of a particular film are indeed expected to be less defective since they grow more slowly.…”
mentioning
confidence: 97%
“…As expected, in the low-energy region ͑a / ഛ0.9͒, the effect of such losses is weak, although it has to be taken into account if a precise description of the measurements is needed. 16,17 For a / ഛ0.9, the band dispersion is almost identical to that of the crystal without extinction: the wave vector may be considered real and linear with frequency, Im͑k͒ becoming significantly larger within the pseudogap. However, well above it, the band structure becomes completely different from that of a crystal without losses ͑see Fig.…”
mentioning
confidence: 98%